Evaluating platelet activation related to the degradation products of biomaterials using molecular markers. Issue 34 (19th August 2020) - Ye, Sheng; Ni, Panxianzhi; Wang, Hong; Yuan, Tun; Liang, Jie; Fan, Yujiang; Zhang, Xingdong
Abstract : The spectra of platelet activation molecular markers were used to study the changes of platelet activation by degradation products. Abstract : Increasing numbers of biodegradable medical devices may be used in the circulatory system. The effects of the released degradation products from these medical devices on the blood may be gradual and cumulative. When they reach critical levels, they may cause thrombosis and other complications. For this reason, it is important to evaluate the blood compatibility of degradation products for quality control and development of these devices. In the present study, we evaluated the degradation products of four biodegradable materials (collagen, polylactic acid, calcium phosphate ceramics, and magnesium) using platelet activation molecular markers that are associated with thrombosis. We found that the degradation products activate platelets to a certain extent, and that the degradation products produced during various degradation time periods activate platelets to varying degrees. This platelet activation occurs via several mechanisms, most of which are associated with the physicochemical properties of the degradation products, including ion concentration, pH, molecular microstructure, and molecular weight. Our findings not only provide a clearer understanding of the effects of degradation products from blood-contacting biodegradable devices, but also provide material for screening of degradation behavior so as to improve quality control for these devices.